2005
DOI: 10.1007/s11156-005-4766-2
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Predictability, Bond Ratings, and Bond Yields

Abstract: We examine the role that earnings predictability plays in establishing a firm’s cost of debt capital by measuring its influence on establishing a new issue’s bond rating. In addition, we also examine the effects of earnings predictability on the initial pricing of the firm’s debt. Using new corporate bond issues from the period 1990–2000, our results indicate that the degree of predictability of a firm’s earnings is positively associated with a firm’s bond rating. Moreover, earnings predictability is also docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…All the models are significant at the .05 level with Likelihood Ratios ranging between 21.9 and 123.5. Our results are comparable to other studies (Blume et al 1998;Crabtree & Maher 2005;Gray et al 2006) that have found debt coverage (OSD), leverage (DA) and profitability (NS) to provide explanatory power in the credit rating process. In addition, the significance of the log of total assets (TA) suggests that larger LPTs will command higher credit ratings, confirming information asymmetry supposition by Krishnaswami et.…”
Section: Or Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…All the models are significant at the .05 level with Likelihood Ratios ranging between 21.9 and 123.5. Our results are comparable to other studies (Blume et al 1998;Crabtree & Maher 2005;Gray et al 2006) that have found debt coverage (OSD), leverage (DA) and profitability (NS) to provide explanatory power in the credit rating process. In addition, the significance of the log of total assets (TA) suggests that larger LPTs will command higher credit ratings, confirming information asymmetry supposition by Krishnaswami et.…”
Section: Or Resultssupporting
confidence: 88%
“…However, there have been inconsistent results in prior literature of using equity beta as a predictor variable in credit rating. Earlier studies (KU) found it to be a significant variable in credit rating prediction, while recent studies (Crabtree & Maher 2005;Gray et al 2006;Maher & Sen 1997) have all found it to be insignificant. As such, our models do not include beta as a predictor variable.…”
Section: Selection Of Variablesmentioning
confidence: 93%
“…This contributes to an understanding of the economic consequences of litigation and determinants of credit rating (Güttler and Wahrenburg, 2007;Jorion et al, 2009;Güntay and Hackbarth, 2010;Afonso et al, 2011). Our findings also address the debate as to whether credit ratings provide useful information to investors (Crabtree and Maher, 2005;Yi and Mullineaux, 2006;Cheng and Neamtiu, 2009; U.S. Department of Justice, 2013). Third, our results show that auditors are more likely to issue unclean opinions 4 about clients involved in patent litigation.…”
Section: Asian Economic and Financial Reviewsupporting
confidence: 55%
“…Prior research finds that entities with more predictable earnings have higher analyst forecast accuracy and lower risk premium in capital markets because higher predictability is seen as a vehicle for increasing transparency of financial information (Graham, Harvey, & Rajgopal, 2005). Since capital market participants can predict future earnings more readily for entities with more predictable earnings, the uncertainty surrounding their earnings tends to be lower and this translates into lower cost of capital (Affleck-Graves, Callahan, & Chipalkatti, 2002;Crabtree & Maher, 2005). Unlike non-financial firms, banks are more sensitive to issues of transparency and uncertainty due to the inherently opaque nature of their operations (Diamond, 1996), growing complexity of operations, and their dependence on large degree of leverage.…”
Section: Earnings Predictabilitymentioning
confidence: 99%